The necessity of financial priority determination to meet the changing needs for goods and services in the public sector - Henama, Bukelwa Lorraine (University of the Free State, 1999)
The legislature of the Republic of South Africa is elected on the basis that it will deliver certain goods and services to the electorate. Financial priority determination ensures that resource allocations are directed towards achieving the results that the government promised the electorate. Through priority determination, state funds are directed according to policy priorities Financial priority determination has been found to be the most difficult part of financial planning and management because it warrants certain expertise from the public officials which this paper addresses in the form of required steps and phases to determine financial priorities. Without the understanding of the phases and steps, priority determination becomes impossible as they determine the criteria used to make decisions. As a result of the changing and increasing needs of the population, the Republic of South Africa experiences severe budget constraints which create the incentive for financial prioritisation, and this forces the departments to evaluate whether their existing policy objectives are still valid, how they have changed and what effect the policy objectives have on programmes. The constraints of the macro-economic policy framework with increasingly lowered deficit targets have also increased the need for prioritisation. It is imperative to consider all the factors that have a bearing on financial priority determination, such as the general environment in which financial priority determination is done; factors that determine the state of community life; needs and expectations of population; policies of the political parties; and research and experiences of public officials. When such factors are taken into account, the process of financial priority determination becomes fair and right. The impact of financial priority determination on the ROP is important because the public sector strives towards reaching the priorities of the ROP. It has been important to reflect on the basic principles and the key programmes of the ROP from which sustainable development has been identified as the ROP priority. Measures have been identified to ensure meeting of sustainable development as an identified ROP priority. Through these measures, sustainable development would be attained. and expected results. This paper points out that in the face of limited resources and the massive demand for public goods and services, it is inevitable that the government cannot hope to meet all the aspirations of the electorate. Instead the government has to choose which sectors must be emphasised in the allocation of resources, indicate from which sectors resources should be withdrawn and redeployed and the order in which these things should be done. This process of choosing which sectors must be emphasised is called financial priority determination. The government policies and strategies to ensure meeting of identified financial priorities in the public sector are tools and instruments through which the public officials could ensure implementation of financial priorities. South Africa is characterised by severe inequalities and poverty of the majority of its inhabitants. Sustainable development is the means through which the society will be relieved of severe poverty although it would be difficult to bridge the inequality gap. Reference has been made to the challenge of economic growth and development facing the Free State Provincial Government to show how this province plans on ensuring economic growth and development. Public officials implement the policy priorities of the government and they have to be guided by basic values and principles to meet the goals of the government. These basic values and principles become the expectations from the public officials in their endeavour to determine financial priorities and in the process of implementing the priorities. This document spells out how financial priority determination is linked with the delivery of public goods and services. If allocation and use of resources is done in an ad hoc manner, without priority determination that could lead to poor public sector performance and the needs of the public would remain unsatisfied. It can be summarised by saying that financial priority determination allows for more effective use of limited resources.
Dissertation (M.P.A. (Public Management))--University of the Free State, 1998
Keywords: Civil Service -- South Africa; Government business enterprises -- South Africa -- Finance; South Africa -- Politics and government